Report of the Ad Hoc committee to study the role of physician's assistants and nurse practitioners in North Carolina - Fagg, John A.; Nelson, David S.; Mauney, F. Maxton; Russ, Donald J.; Estes, E. Harvey (Edward Harvey), 1925- (1980)
A summary report of the Ad Hoc Committee to Study the Role of Physician's Assistants and Nurse Practitioners in North Carolina presented to the NC Medical Society in 1980. The report basically calls for no change in the NC Medical Society's policy related to PAs and NPs. It reminds physicians of their responsibility in employing and using PAs and NPs in their practices.